2006
DOI: 10.1055/s-2006-942146
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Navigation: An Accepted Standard of Care?

Abstract: It is still not generally considered common practice to use spinal navigation as an aid for the implantation of pedicle screws. Most pedicle screws are still inserted conventionally. Although nearly 50 % of German neurosurgeons believe that spinal navigation could enhance safety when placing pedicle screws, they clearly reject efforts to make spinal navigation mandatory. With only one exception, the German neurosurgical community unanimously rejects the idea that placing pedicle screws without spinal navigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In recent years, 3-dimensional image intensifiers, intraoperative CT and navigation systems have been established and several authors have reported reduced rates of malpositioned pedicle screws when employing these systems. While these technologies are disputed, they appear to be the method of choice in our opinion, at least in the long-term perspective [4,8].…”
Section: Discussionmentioning
confidence: 90%
“…In recent years, 3-dimensional image intensifiers, intraoperative CT and navigation systems have been established and several authors have reported reduced rates of malpositioned pedicle screws when employing these systems. While these technologies are disputed, they appear to be the method of choice in our opinion, at least in the long-term perspective [4,8].…”
Section: Discussionmentioning
confidence: 90%
“…Difference of opinion is expected amongst neurosurgeons versus orthopedic surgeons as to what constitutes surgical excellence [26]. Schroder and Wassman [27] point to a range of opinion amongst German neurosurgical departments about navigation technology for insertion of pedical screws ranging from "not useful at all" to "malpractice if not using it". They also found that opinion was divided on the safety benefits of using neuro-navigation for spinal surgery with 49% responding that it enhances safety whereas 37% reported that it did not and 14% were unsure.…”
Section: Review Of Success Criteramentioning
confidence: 99%
“…15,16 However, CAN is used routinely by only 10-15% of spinal surgeons. [17][18][19] A worldwide survey of spinal surgeons, representing predominantly Europe, Asia, and Latin America, revealed multiple barriers to CAN adoption, principally cost, lack of training, workflow disruption, and unproven clinical benefit. 17 The potential benefit of intra-operative CAN for trainee education is also poorly represented in assessments of spinal CAN utility.…”
Section: Introductionmentioning
confidence: 99%